PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN MELALUI STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA ( BEI ) - Brigitta Clarabella Petta; Josua Tarigan (Business Accounting Review, 2017)
This research aimed to know the influence of institutional ownership towards financial performance with capital structure as an intervening variable, this kind of research that used capital structure as intervening variable, was not done before. This research used 89 manufacturing companies listed in Indonesia Stock Exchange, during the period of 2011-2015 as the sample. Data collected from annual reports of the period 2011-2015 and was analyzed by using WarpPLS software version 5.0. According to the data, this research showed there was a high level of institutional ownership among the manufacturing companies in Indonesia. This high level of institutional ownership maximized the financial performance of the firms and minimized the conflict of interest in the firm. Furthermore, institutional ownership was able to minimize the debt in capital structure because of the monitoring role of creditor was redirected to institutional investor. Moreover the use of debt in capital structure was able to decrease the firm’s financial performance due to the higher risk of the firms.